A mechanistic model for carbon steel corrosion rate in aqueous carbonated solution of activated mdea and activated dea / Lubna Ghalib Abdulkhaleq - Lubna Ghalib, Abdulkhaleq (2016)
Corrosion constitutes a major operational difficulty in CO2 absorption plants using aqueous amine solutions and has a significant impact on the plant's economy. It is a complex phenomenon in which transport, electrochemical and chemical processes occur simultaneously and interactively. It is difficult to control corrosion problems in a cost-effective manner as knowledge of corrosion in this system is limited and inconclusive. Thus, the purpose of this work is to obtain a better understanding of corrosion process in an aqueous activated amine based CO2 environment. A mechanistic corrosion model was built using Matlab software, to predict corrosion rate of carbon steel in the carbon dioxide (CO2) absorption processes using aqueous solutions of activated Methyl-di-ethanolamine and activated Diethanolamine, to identify the oxidizing agents responsible for corrosion reactions when no protective films are present. The developed corrosion model takes into account the effects of fluid flow on the corrosion process. The electrochemical corrosion model takes into account charge transfer and diffusion of oxidizing agents. This work provides comprehensive information on the corrosion behavior of carbon steel in an aqueous carbonated solution of activated Methyl-di-ethanolamine and activated Diethanolamine systems. The model comprises two main models, i.e. Vapor-liquid equilibrium model and electrochemical corrosion model. The rigorous electrolyte-NonRandom Two Liquid model was built into the model in order to determine the concentrations of chemical species in the bulk solution. The speciation results from electrolyte-nonrandom two liquid equilibrium model were subsequently used for generating polarization curve and predict the corrosion rate taking place at the metal surface. iv The direct impact of the important process parameters were investigated by conducting corrosion modeling using electrochemical polarization technique under a wide range of input conditions. Corrosion rates are predicted based on the input data required for model simulation such as solution temperature, CO2 partial pressure, amine concentration, electrode rotating speed and pipe diameter. The output from the model simulation can be presented as species concentration in the bulk solution, CO2 loading, corrosion potential, corrosion rate, and polarization curves. Predictions of the present corrosion model were compared to the experimental corrosion data from literature and generally good agreement was achieved. Simulation results show that the corrosivity order of CO2 amines in carbon steel was governed mainly by their CO2 loading; higher CO2 absorption capacity such absorption led to higher corrosion rate. For activated amine mixtures, the data showed that a reduction in carbon steel corrosion rate of MDEA-PZ system when keeping the total amine concentration at 2 M and varying the activator and the base amine concentrations. However, for DEA-PZ the data showed an increase in carbon steel corrosion rate, the corrosion rates were evaluated under the same operating conditions (CO2 loading, solution temperature and amine concentration) for both systems. At low CO2 loading, low solution temperature, and low activator concentration, the order of the corrosivity of the systems is as follows: MDEA-PZ is greater than that of DEA-PZ. Whereas at high conditions of CO2 loading, solution temperature and activator concentration, the corrosivity ranked is opposite to that of lower conditions.